Effect of environmental knowledge and concern toward attitude of green home buyers’ intention in Surabaya - Wijayaningtyas, M. (CRC Press/Balkema, 2016)
Understanding consumers’ buying behaviour, as one of the important elements for green homes market growing, could increase green homes development in Surabaya. From previous studies in consumers’ buying behaviour of green products shows that they were influenced by Environmental Knowledge (EK), Environmental Concerns (ECs), and attitude. Meanwhile, attitude affects a person’s intention to perform behaviour; in the context of this paper is the behaviour of green home consumers’. Therefore, this study has an objective to examine the effect of EK and concern toward attitude on green home buyers’ intention. The data collection has gathered from 240 prospective home buyers. The findings of this study; first, the model shows that the measured variables is fit to empirical data in the field. Second, that EC has strong significant than EK toward attitude. Third, attitude toward green home has significant effect toward green home buyers’ intention.